Domesticity at War - Colomina, Beatriz (Barcelona : Actar D, 2006)
Built in the USA -- 1949 -- DDU at MoMA -- The Eames House -- The lawn at war -- X-ray architecture -- Unbreathed air -- Enclosed by images -- The underground house
boek